Gondolatok az ingatlan kiürítés végrehajtásához - polgári peres vagy nemperes eljárás - - Kavecsánszki, Éva (Debreceni Jogi Műhely, 2019)
In many cases, owners have problems recovering their rented or arbitrarily occupied real estate. News often report difficult situations in connection with the evacuation of real estate. More instructive cases have also drawn attention to the severity of the problem. The study describes the rules for (litigation and non-litigation) court proceedings for the evacuation of real estate and does not deal with the enforcement procedures ordered by a notary. The possibility to initiate emptying real estate non-litigation procedure - according to Vht. 183rd-184th § - is not well known widely. According to most people, almost the only possible way to reclaim the real estate is to litigate, although the possibility of initiating the non-litigation procedure has been provided for years, provided the conditions of the law are met. Emptying of real estate in non-litigious procedure is possible in the case of real estates by arbitrarily occupied real estates, fixed-term tenancy agreemens of residential premises and other non-residential premises, as well as other types of properties specifically designated by law. The study presents the possible ways of carrying out the real estate evacuation, the enforcement procedure following the litigation procedure and the enforcement procedure initiated on the basis of a court non-litigation procedure, focusing primarily on proceedings commenced after 1. January 2018. The study deals with the legal background to the non-litigation and litigation procedure, the order for enforcement, the issuing, the service of an enforceable instrument, the possibilities provided by law in the event of non-execution, the short presentation of remedies. It also deals with some of the innovations introduced by law CXXX of 2016 on Civil Procedure Rules, suspension of enforcement, as well as the applicability of the eviction moratorium in each case. In the emptying of real estate, debtors often face criminal law. The most frequent criminal cases during the emptying of the real estate are presented in the study too (breach of seal, assault on a public official).